Haiti : 2012 Article IV Consultation and Fifth Review Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2013)
Significant progress has been made in Haiti to safeguard macroeconomic stability after the January 2010 earthquake. However, the pace of the reconstruction has been slow and the business environment remains unattractive. Further development and strengthening social safety nets are essential. The monetary policy stance is appropriate and continuing commitment to exchange rate flexibility is appreciated. Improving the business environment is important to raise productivity, enhance competitiveness, and achieve higher and more inclusive growth.